2009
DOI: 10.1177/0020764008095114
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Study of Female Delinquent Adolescents in a Detention Centre: Effectiveness of Psychiatric Intervention as a Mental Health Service

Abstract: Results of this study showed that the time course and psychiatric intervention contributed to recovery of depression and therapeutic intervention. The time course might reduce eating problems. Psychiatric intervention might be necessary for female juvenile detainees, which presents an important issue for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…When the mean total score of the BIS-11 scale in our population is compared with results from other non-clinical samples (Fossati et al, 2002;Leshem and Glicksohn, 2007;Patton et al, 1995;Soeiro-De-Souza et al, 2013), we observed a relatively low mean for BIS total score in our subjects. None of the previous studies using BIS-11 in PTSD subjects adopted a cut-off (Ariga et al, 2010;Depue et al, 2014;Oquendo et al, 2005;Moeller et al, 2001;Nelson et al, 2013;Swick et al, 2013), which results in the absence of previous parameters for comparison. Our result (15.9% of the population presented high impulsivity, and 14% presented low impulsivity) seems to be coherent with the clinical background.…”
Section: Discussionmentioning
confidence: 99%
“…When the mean total score of the BIS-11 scale in our population is compared with results from other non-clinical samples (Fossati et al, 2002;Leshem and Glicksohn, 2007;Patton et al, 1995;Soeiro-De-Souza et al, 2013), we observed a relatively low mean for BIS total score in our subjects. None of the previous studies using BIS-11 in PTSD subjects adopted a cut-off (Ariga et al, 2010;Depue et al, 2014;Oquendo et al, 2005;Moeller et al, 2001;Nelson et al, 2013;Swick et al, 2013), which results in the absence of previous parameters for comparison. Our result (15.9% of the population presented high impulsivity, and 14% presented low impulsivity) seems to be coherent with the clinical background.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of recidivism in violent women has been observed to be high, especially if they are young or if they have been diagnosed with drug addiction or personality disorders such as depressive and behavioural disorders, as well as a high impulsiveness (Ariga et al, 2010;Putkonen, Komulainen, Virkkunen, Eronen, and Lo nnqvist, 2003;Salom et al, 2014). Actually, violent women and men who also suffer from personality disorders are comparable in the risk of recidivism (23% versus 26%, respectively) (Putkonen, Komulainen, Virkkinen, Eronen and Lönnqvist, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical basis supports the effectiveness of informal processing and non-placement sentencing in order to reduce recidivism (Howard, 1963;Soulier & Scott, 2010). However, research identifying effective processing and sentencing on preventing recidivism has conflicting findings or demonstrates low feasibility for practical implementation within the juvenile justice setting (Ariga et al, 2010;Bergseth & Bouffard, 2012;Henggeler, Melton, Brondino, Scherer, & Hanley, 1997;Lipsey & Wilson, 1998;Livingstone, Macdonald, & Carr, 2013;McGrath & Weatherburn, 2012). Furthermore, to our knowledge, no study to date has assessed the impact of the juvenile justice system on recidivism among young offenders in a rural setting.…”
Section: Juvenile Offenders and Recidivismmentioning
confidence: 99%
“…Youth within placement represent a high risk population characterized by a high prevalence of mental health illnesses and trauma (Espinosa, Sorensen, & Lopez, 2013). Among detained girls, up to 78% were diagnosed with a mental health disorder and up to 84% reported experiencing at least one violent traumatic event (Ariga et al, 2010;Lederman, Dakof, Larrea, & Li, 2004). Some of these traumatic events originate in the facility; 12% reported experiencing sexual victimization perpetrated by staff or another youth offender during placement (Beck, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation